Entrepreneurship development and employment generation in delta state through business education - Usioboh, Sunday Abumhenre (Journal of Professional Secretaries and Office Administrators, 2014)
This paper took a study of Delta State growing unemployment situation and how it increasingly dwindles its potentials. This paper is focused on entrepreneurship development and business education as a panacea for reducing unemployment in Nigeria. A well structured four-point Likert Scale questionnaire was administrated to elicit responses from the selected samples. The sample consisted of 230 Business Education students, Degree Programme. The proportionate stratified random technique was used to select 150 accounting major and 80 secretarial major students of business education department. The student-mix consisted of 86 male and 144 female. The data collected were analyzed using Z-test statistics at = 0.05. It was found that both accounting and secretarial students are for now not keen on establishing their own businesses after graduating, even with business and entrepreneurial education because of the capital needed. They prefer to be job seekers rather than becoming entrepreneurs. It was also discovered that male and female business education students are not equally interested in going into entrepreneurship. Consequently, it was recommended inter alia that feasibility study report for a potential business should be made mandatory for all business education students before graduation. It was also recommended that government should award best graduating students with start-up capital to enhance entrepreneurship development.